ASSESSMENT OF THE DYNAMICS OF INTERNATIONAL TOURISM DEVELOPMENT IN UKRAINE (INNOVATIVE ECONOMY, 2024)
Mazur V.S., Halko O.V. ASSESSMENT OF THE DYNAMICS OF INTERNATIONAL TOURISM DEVELOPMENT IN UKRAINEPurpose. The aim of the article is to define the level of potential for the continuous development of the tourism industry and close interaction with various sectors of the economy, making it a significant component in the social and economic life of countries and peoples (communities).Methodology of research. Both general scientific and specialized methods were utilized in the research process, including: induction and deduction – during the collection, systematization, and processing of necessary information; analysis and comparison – in reflecting the development of international tourism in Ukraine compared to other countries worldwide and within the region; abstract and logical – for forming theoretical conclusions; monographic and comparative – for systematizing scientific approaches of scholars to the theoretical aspects of tourism business development; graphical – for visualizing research results.Findings. The article discusses a scientific investigation into various aspects of international tourism development. It differentiates various definitions of "tourism" found in publications, which help identify the direction of further research in this field. It is determined that international tourism is one of the key sectors of foreign economic activity, demonstrating the highest growth dynamics. Seven main factors contributing to the growth of international tourism are outlined. An analysis of the situation in the domestic market of tourist services for the years 2019-2022 is conducted, supported by statistical data and the State Agency for Tourism Development (SATD). Challenges are assessed, including the pandemic and full-scale military aggression by Russia against Ukraine.It is identified that tourism could become one of the sectors enabling Ukraine to recover after the crisis.Originality. The author's approach to the interpretation of the main approaches to understanding the tourism industry has been further developed. The main factors of growth of international tourism against the background of strengthening quarantine measures in individual countries and regions are identified. An in-depth assessment of the impact of the COVID-19 pandemic and full-scale war on the tourism market of Ukraine is carried out.Practical value. The proposed proposals for assessing the dynamics of international tourism development in Ukraine can be used by public authorities, travel companies and other stakeholders to develop a strategy for the development of international tourism in Ukraine.Key words: international tourism, tourist industry, foreign economic activity, tourism potential, recreation, tourist flows, infrastructure, influencing factors.
Keywords: international tourism; tourist industry; foreign economic activity; tourism potential; recreation; tourist flows; infrastructure; influencing factors.